Improving mathematics learning outcomes of first-grade students with additional material using the STAD model at SDN Srengseng Sawah 04 South Jakarta - Rosliani, Okta; Yusnita, Erni; Latifah, Syarfi Nia; Kurniawati, Armilia; Ramadhan, Alif Fajar (Perkumpulan Peneliti Pendidikan dan Pengembangan Anak, 2024)
This study used data from observations of first-grade primary school pupils at SDN Srengseng Sawah 04 South Jakarta in the 2017–2018 academic year who still had learning outcomes in the mathematics topic of addition material that fell short of the KKM norm. This study aimed to improve the learning outcomes of grade I children in math addition material. This study employs a cycle approach of classroom planning, implementation, observation, and reflection as its methodology. Thirteen class I B students, sixteen of whom were male and fifteen of whom were female, made up the subjects of this study. Their backgrounds varied concerning place of residence, social standing, and academic accomplishment. Pre-cycle findings showed 48.4% completeness, while cycle one completeness of student scores was 64.52%; cycle 2 data showed an average score of 96.77%. We can conclude that bettering student learning outcomes through a cooperative learning approach is possible.